Design of an electronic device based on cyclic actions as an entertainment tool for social inclusion to people on quadriplegia condition - Munevar, Pablo Antonio Gelvez; C, Harold Michel Torres; Mñoz, Juan Carlos Moreno; Rojas, Luis Eduardo Bautista (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Social inclusion is a social development fundamental factor. People with disabilities are excluded from collective environments, in Colombia there are about 260,000 quadriplegia cases, a physical disability caused by paralysis in trunk, legs and arms. This paper presents a device design, oriented to physical and emotional development generated by entertainment, allowing to user in disadvantage, integration with household people, via a video game. BUCLE is a control device, which identifies the cervical spine movements as interaction commands in a video game. This device was evaluated by 10 people, one of them on quadriplegia condition. It was observed that the user interacting with the interface maintains the display without any problem, also a difference of only 5% efficiency with respect to commands made by people without physical limitations is observed.